Controlling the Charge Transfer across Thin Dielectric Interlayers. Issue 14 (27th May 2020) - Hurdax, Philipp; Hollerer, Michael; Puschnig, Peter; Lüftner, Daniel; Egger, Larissa; Ramsey, Michael G.; Sterrer, Martin
Abstract: Whether intentional or unintentional, thin dielectric interlayers can be found in technologies ranging from catalysis to organic electronics. While originally considered as passive decoupling layers, recently it has been shown that they can actively promote charge transfer from the underlying metal to adsorbates. This charging can have profound effects on the surface chemistry of atoms, atomic clusters, and molecules, their magnetic moments, and charge injection at the contacts of organic devices. Yet, controlled studies required to understand the charge transfer process in depth are still lacking. Here, a comprehensive analysis of the phenomenon of charge transfer using the atomically controlled system of pentacene on ultrathin MgO(100) films on Ag(100) is presented. It is shown that the charge transfer process is governed by the charged and uncharged molecular species with distinct energy levels in the first monolayer. The experimental approach applied in this work allows to observe and control their ratio through direct tuning of either the work function or the thickness of the dielectric interlayer. Abstract : Integer charge transfer from a metal through a dielectric interlayer into adsorbed pentacene is studied using ultrathin MgO(100) films on Ag(100). The potential equilibration of Fermi level alignment for organic films is goverend by the portion of singly charged and uncharged molecules in the first monolayer, which can be controlled by the work function and the thickness of the dielectric.